Foreign language anxiety and translanguaging as an emotional safe space: Migrant English as a foreign language learners in Australia - Dryden, Stephanie; Tankosic, Ana; Dovchin, Sender (ELSEVIER SCI LTD, 2021)
Foreign language anxiety (FLA) is a negative emotional reaction that many migrant English as a foreign language (EFL) learners encounter when learning or using English in a host society. Using Linguistic Ethnography (LE), we investigate how four migrant adult EFL learners in Australia (1) experience the negative emotional reactions of FLA such as “forgetfulness”, “feelings of isolation”, and “self-avoidance”, as well as strong emotional outbursts such as crying and weeping; and (2) how the use of translanguaging may correspondingly work as emotional safe spaces to mitigate these negative reactions of FLA. The implications of this study show the importance of safe educational and emotional spaces for migrant background EFL learners, where such spaces can allow EFL learners to authentically share their lived experiences, problems, and emotional expressions through translanguaging, which can assist in the alleviation of the negative emotional reactions of FLA.